Global bond portfolios and EMU - Philip R. Lane (European Central Bank (ECB), 2005)
We examine the bilateral composition of international bond portfolios for the euro area and the individual EMU member countries. We find considerable support for “euro area bias”: EMU member countries disproportionately invest in one another relative to other country pairs. Another striking pattern is the positive connection between trade linkages and financial linkages in explaining asymmetries across EMU member countries in terms of their outward and inward bond investments vis-à-vis external counterparties. At the aggregate level, it is those countries physically closest to the euro area that are both the most important destinations and sources for external bond investment vis-à-vis the euro area. Our empirical results support the notion that financial regionalization is the leading force underlying financial globalization.
Keywords: E4; F2; F3; F4; 330; bond portfolios; EMU; financial integration; Rentenmarkt; Portfolio-Management; Eurozone; Internationaler Finanzmarkt; EU-Staaten